2003
DOI: 10.1093/humupd/dmg043
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of placental development and endocrine functions between the human and mouse model

Abstract: The placenta plays a key role in pregnancy, mediating exchanges between mother and fetus and maternal tolerance of fetopaternal antigens. In some species, it also produces hormones that ensure the maintenance of gestation and fetal well-being. This unique organ also has considerable potential for use as a model for various aspects of biology. Indeed, the use of transgenic mouse models has greatly improved our understanding of the genetic control of placental development in this species and has opened up new ®e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
306
2
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(334 citation statements)
references
References 111 publications
(100 reference statements)
11
306
2
15
Order By: Relevance
“…[19][20][21][22] We discontinued progesterone at 12 weeks of gestation but consider it unlikely that therapy beyond this time would result in better outcomes; it is well documented that corpus luteal function is replaced by placental production of progesterone before the end of the first trimester. 3 Moreover, among PROMISE participants who had a miscarriage, the median gestation was less than 8 weeks (7.3 weeks in the progesterone group and 7.1 weeks in the placebo group).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[19][20][21][22] We discontinued progesterone at 12 weeks of gestation but consider it unlikely that therapy beyond this time would result in better outcomes; it is well documented that corpus luteal function is replaced by placental production of progesterone before the end of the first trimester. 3 Moreover, among PROMISE participants who had a miscarriage, the median gestation was less than 8 weeks (7.3 weeks in the progesterone group and 7.1 weeks in the placebo group).…”
Section: Discussionmentioning
confidence: 98%
“…If implantation occurs, the corpus luteum continues to produce progesterone, but between 8 and 12 weeks of gestation, the placenta takes over this role and maintains the pregnancy thereafter. 3 The physiological importance of progesterone in early pregnancy has prompted the performance of several trials to evaluate the effect of progesterone supplementation in the first trimester of pregnancy among women with a history of recurrent miscarriages. A Cochrane review of four small trials showed a significantly lower risk of miscarriages among women who received progesterone than among those who received placebo or no treatment (odds ratio, 0.39; 95% confidence interval [CI], 0.21 to 0.72), but the quality of the four trials was considered to be poor.…”
mentioning
confidence: 99%
“…iii) invasão e remodelação do endométrio decidualizado e de sua vasculatura pelas células do trofoblasto; iv) estabelecimento da placenta (Revisão em: Georgiades et al, 2002;Malassine et al, 2003). (Bevilacqua, Abrahamsohn, 1988;Revisão em: Cross et al, 1994;Malassine et al, 2003;.…”
Section: Implantação Embrionáriaunclassified
“…(Bevilacqua, Abrahamsohn, 1988;Revisão em: Cross et al, 1994;Malassine et al, 2003;. Considerando que a organogênese compreende o período entre o 7º e o 12º dg , grande parte deste processo ocorre enquanto o embrião é nutrido pela placenta corio-vitelínica, enfatizando a sua importância para o desenvolvimento embrionário em camundongos.…”
Section: Implantação Embrionáriaunclassified
See 1 more Smart Citation